CONCUR 2014 - Concurrency Theory 25th International Conference, CONCUR 2014, Rome, Italy, September 2-5, 2014. Proceedings. - Baldan, Paolo (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the refereed proceedings of the 25th International Conference on Concurrency Theory, CONCUR 2014, held in Rome, Italy in September 2014. The 35 revised full papers presented together with 5 invited talks were carefully reviewed and selected from 124 submissions. The focus of the conference is on the following topics: process calculi, model checking and abstraction, synthesis, quantitative models, automata and multithreading, complexity, process calculi and types, categories, graphs and quantum systems, automata and time, and games.